The most requested imaging tests in the treatment of aneurysmal bone cyst and their relationship to outcome: an update - Ruivo Biancardi, Mariel; Brito Reia, Verônica Caroline; Peralta-Mamani, Mariela; Silva Santos, Paulo Sérgio; Fischer Rubira-Bullen, Izabel Regina (Revista Estomatológica Herediana, 2023)
This study aimed to review the most required imaging tests, their characteristics, and whether the primary choice is sufficient for lesion management. PubMed, Web of Science, and Scopus databases were searched. The included articles were case reports or series of aneurysmal bone cysts in the mandible or maxilla that had all the information about the case, from diagnosis to follow-up. The 32 included articles showed that the first imaging test required is a panoramic radiographic examination of the cases, with only a few choosing computed tomography as the first option. The treatment of choice is usually curettage, and 9 cases had recurrences, although 17 did not report follow-up. 2D imaging examinations were the most required type when diagnosing an aneurysmal bone cyst, but 3D examinations were necessary in many cases for better evaluation and to provide more details.